Structural and optical properties of TiO₂ and ZrO₂ nanoparticles and TiₓZr₁-ₓO₂ nanocomposites in relation to thermal-treatment method - Keiteb, Aysar Sabah (2016)
Metal oxide nanoparticles hold a great scientific and technological interest due to their unique physical and chemical properties arise from their nanoscale dimension and large number of surface atoms. As their properties are dependent on large surface area to volume ratio and quantum confinement effect, they have potential applications in almost every field of technology. Several methods have been employed previously to synthesize metal oxide nanoparticles with enhanced chemical and physical properties. However, most of these methods have used a complicated procedure, longer reaction times, employed toxic reagents and produced by-products which are not environmentally friendly. Current study employed thermal treatment method to prepare TiO2 and ZrO2 nanoparticles and Tix Zr1-xO2 nanocomposites (x= 0.9, 0.7, 0.5 0.3 and 0.1) directly from surfactant solution without any drying prior to calcination process. An aqueous solution contains of metal precursors, poly(vinyl) pyrrolidone as a capping agent and deionized water as a solvent. The precursors solution underwent calcination at temperatures ranging from 500 to 800 oC. The physical structural, elemental composition, phase composition, morphological and optical properties of the synthesized nanoparticles/nanocomposites were investigated using energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), powder X-ray diffraction (XRD), and UV-Vis spectrometer. A thermogravimetric analyzer (TGA) was used to study thermal stability and the removal of polymer from the samples while being calcined. Full decomposition of the polymer was found at 488 oC. The FTIR results confirmed the removal of the polymer along with organic matter and the existence of metal oxide nanoparticles at 500-800 oC. The elemental composition of the sample obtained by EDX spectroscopy has confirmed the formation of Tix Zr1-xO2 nanoparticles. The XRD diffraction patterns at calcination temperatures 500-800 oC showed that the crystallite sizes for TiO2 nanoparticles were in the range of ~5–27 nm with tetragonal structure, ~4-16 nm with a face-centered cubic structure for ZrO2 nanoparticles and in the range of 5-23 nm for tetragonal mixed cubic structure of Tix Zr1-xO2 nanocomposites. These results were further proved by TEM results which showed that the formation of metal oxide has taken place in nanoscale size. The optical band gap of the samples calculated using Kubelka-Munk equation varied from 3.55 to 3.40 eV for TiO2 nanoparticles, 4.88 to 4.71 eV for ZrO2 nanoparticles, and 5.21-3.50 eV for Tix Zr1xO2 nanocomposites and calcination temperatures 500-800 oC. This is the results of the average particle sizes determined by TEM images, which were found to be increasing with increased calcination temperatures from 6 to 30 nm for TiO2 nanoparticles, 5 to 18 for ZrO2 nanoparticles and 4-25 nm for Tix Zr1-xO2 nanocomposites. The reason for this is that the quantum confinement effect takes place whereby for the smaller particle size, the interaction between outer electrons and ions (protons) is weaker that leads to larger band gap energy and for the larger particle size the interaction between outer electrons and ions (protons) is stronger that leads to smaller band gap energy.